Korupsi dan Perlunya Teologi Baru di Sektor Publik - Saefur Rochmat (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2006)
New theology of public sphere pretends to counter secularism in modem era by breaking the separation wall of public and private affairs. It agrees with the secularization of public affairs which separates the management of public affairs of the state with that of the private affairs of religion, hut both should develop dialogue to build humanistic civilization. Islam should revitalize its legal Islamic law (fiqh) in order not to emphasize its orientation to Pillars of Islam (Rukun Islam / community sector, but try to make balance with Pillars of Belief (Rukun Iman/private sector). It will result in Pillars of Public Sector as a kind of intermingle between Rukun Islam and Rukun Iman.